Metus pyrrhicus : rzeczywistość i historiografia - Wolny, Miron (Instytut Historyczny Uniwersytetu Wrocławskiego, 2019)
The main issue of this article is the question of the social impact of the war against Pyrrhus in Rome. The author analyzes the problem of fear of Pyrrhus (metus Pyrrhicus). The image of Pyrrhus was created based on Greek literary standards